Reliability of Telecommunications Systems Following a Major Disaster: Survey of Secondary and Tertiary Emergency Institutions in Miyagi Prefecture During the Acute Phase of the 2011 Great East Japan Earthquake. Issue 2 (21st February 2014) - Kudo, Daisuke; Furukawa, Hajime; Nakagawa, Atsuhiro; Abe, Yoshiko; Washio, Toshikatsu; Arafune, Tatsuhiko; Sato, Dai; Yamanouchi, Satoshi; Ochi, Sae; Tominaga, Teiji; Kushimoto, Shigeki
Abstract Introduction Telecommunication systems are important for sharing information among health institutions to successfully provide medical response following disasters. Hypothesis/Problem The aim of this study was to clarify the problems associated with telecommunication systems in the acute phase of the Great East Japan Earthquake (March 11, 2011). Methods All 72 of the secondary and tertiary emergency hospitals in Miyagi Prefecture were surveyed to evaluate the telecommunication systems in use during the 2011 Great Japan Earthquake, including satellite mobile phones, multi-channel access (MCA) wireless systems, mobile phones, Personal Handy-phone Systems (PHS), fixed-line phones, and the Internet. Hospitals were asked whether the telecommunication systems functioned correctly during the first four days after the earthquake, and, if not, to identify the cause of the malfunction. Each telecommunication system was considered to function correctly if the hospital staff could communicate at least once in every three calls. Results Valid responses were received from 53 hospitals (73.6%). Satellite mobile phones functioned correctly at the highest proportion of the equipped hospitals, 71.4%, even on Day 0. The MCA wireless system functioned correctly at the second highest proportion of the equipped hospitals. The systems functioned correctly at 72.0% on Day 0 and at 64.0% during Day 1 through Day 3. The main cause of malfunction of the MCA wireless systems was damage to the base station or communication lines (66.7%). Ordinary (personal or general communication systems) mobile phones did not function correctly at any hospital until Day 2, and PHS, fixed-line phones, and the Internet did not function correctly at any area hospitals that were severely damaged by the tsunami. Even in mildly damaged areas, these systems functioned correctly at <40% of the hospitals during the first three days. The main causes of malfunction were a lack of electricity (mobile phones, 25.6%; the Internet, 54.8%) and damage to the base stations or communication lines (the Internet, 38.1%; mobile phones, 56.4%). Conclusion Results suggest that satellite mobile phones and MCA wireless systems are relatively reliable and ordinary systems are less reliable in the acute period of a major disaster. It is important to distribute reliable disaster communication equipment to hospitals and plan for situations in which hospital telecommunications systems do not function. <mixed-citation id="ref" publication-type="journal"> <string-name> <given-names>D</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Kudo</surname> </string-name>, <string-name><given-names>H</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Furukawa</surname></string-name>, <string-name><given-names>A</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Nakagawa</surname></string-name>, <string-name><given-names>Y</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Abe</surname></string-name>, <string-name><given-names>T</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Washio</surname></string-name>, <string-name><given-names>T</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Arafune</surname></string-name>, <string-name><given-names>D</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Sato</surname></string-name>, <string-name><given-names>S</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Yamanouchi</surname></string-name>, <string-name><given-names>S</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Ochi</surname></string-name>, <string-name><given-names>T</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Tominaga</surname></string-name>, <string-name><given-names>S</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Kushimoto</surname></string-name>. Reliability of telecommunications systems following a major disaster: survey of secondary and tertiary emergency institutions in Miyagi Prefecture during the acute phase of the 2011 Great East Japan Earthquake . <source>Prehosp Disaster Med</source>. <year>2014</year>;<volume>29</volume>(<issue>1</issue>):<fpage>1</fpage>-<lpage>5</lpage></mixed-citation>.